Venturing the Golden Indonesia 2045: Are Electricity and Broadband Development for Five Indonesian Priority Industries Impactful? - Arif Zeinfiki Djunaedi; Kautsar Riza Salman; Heri Supriyanto (Journal of Economics, Business, and Accountancy Ventura, 2024)
This study aims to examine the impact of electricity and broadband development on the progress of five priority industries in Indonesia. Initial findings indicate a mismatch between policy expectations and their impacts. This research collected secondary data from 2010 to 2019, using a time series approach and bootstrapping 1000 times to strengthen and cover the weaknesses of the method and the short time span. The results reveal that the electronics sector has the greatest beneficial impact both partially and simultaneously from all external variables. Additionally, four industries, except the automotive sector, show the same impact. This report emphasizes the necessity of synergy between digitalization and electrification, asserting the inseparable integration of policies. The automotive sector has experienced significant growth over the past decade, but it has not been directly impacted by these policies. Conversely, the food industry is affected and has emerged as the largest output producer, while other sectors are considered to have growth potential, indicating the need for alternative infrastructure initiatives. This study is expected to provide insights to all stakeholders regarding the impact of government policies and how to maximize business benefits amid global challenges.